PERHITUNGAN KONSUMSI BAHAN BAKAR PADA HD 465 -7R MENGGUNAKAN METODE RPM MESIN DAN PENDEKATAN PER SEGMENT PADA PERUSAHAAN PERTAMBANGAN DI KALIMANTAN TIMUR - Pranajiwa; Shalaho Dina Devy; Albertus Juvensius Pontus; Windhu Nugroho; Harjuni Hasan (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2024)
Fuel is usually used by engines to move or do work. In this article, the machine is a mining industry vehicle with the code HD 465 – 7R type from the Komatsu company. The vehicle is used to move overburden material from the loading area to the disposal area. Fuel consumption is usually influenced by several factors, the most influential of which are the slope of the road, the type of material used for the road, and the distance from the loading place to the dumping place. There are several methods are used to calculate fuel consumption, the most familiar of which is the vehicle working hours (hour meter) method. In this research, the calculation of fuel consumption uses engine RPM with a segment approach method taken with a segment distance of between 100 - 200 meters. The results of calculating fuel usage on the HD 465 – 7R have a figure of 51.7 liters/hour, with the actual value being 51.9 liters/hour. The conclusion of this research is that by using the engine RPM method, the results of fuel usage calculations are also close to the actual values. Testing by RPM with an hour meter is very different, where testing by RPM is based on the length of duration at that RPM number; the higher the RPM and the longer the duration of time, the greater the fuel released. This is continuous with the road segment, where an uphill road segment will definitely increase travel time due to a decrease in speed, and the RPM will increase.